Speed up society? Evidence from the UK 2000 and 2015 time use diary surveys - Alon, O; Gershuny, J (SAGE Publications, 2017)
Using time diary evidence on change in the frequency and distribution of activities from UK time diary data over the 15 years from the turn of the 21st Century, we assess whether the thesis of ‘the speed-up society’ is manifested in an increase in time intensity in people’s daily lives. Comparing indictors like time fragmentation, multitasking, and ICT use, to respondents’ reports of how rushed they normally feel, we find no evidence that time pressure is increasing, or that ICT use is associated with greater feelings of time pressure. Rather, we find consistent cross-sectional differentials in our measures of time intensity by gender and occupational status, supporting the idea of relative stasis in the underlying social inequalities of time. These findings are consistent with previous research based on time use data, and we pose them as a challenge to theories of societal speed-up.